Effect of CpG Depletion of Vector Genome on CD8+ T Cell Responses in AAV Gene Therapy - Bertolini, Thais B.; Shirley, Jamie L.; Zolotukhin, Irene; Li, Xin; Kaisho, Tsuneyasu; Xiao, Weidong; Kumar, Sandeep R. P.; Herzog, Roland W. (Frontiers in Immunology, 2021)
Adeno associated viral (AAV) vectors have emerged as a preferred platform for in vivo gene replacement therapy and represent one of the most promising strategies to treat monogenetic disorders such as hemophilia. However, immune responses to gene transfer have hampered human gene therapy in clinical trials. Over the past decade, it has become clear that innate immune recognition provides signals for the induction of antigen-specific responses against vector or transgene product. In particular, TLR9 recognition of the vector’s DNA genome in plasmacytoid dendritic cells (pDCs) has been identified as a key factor. Clinical trial data and pre-clinical animal studies implement CpG motifs in the vector genome as drivers of immune responses, especially of CD8+ T cell activation. Here, we demonstrate that cross-priming of AAV capsid-specific CD8+ T cells depends on XCR1+ dendritic cells (which are likely the main cross-presenting cell that cooperates with pDCs to activate CD8+ T cells) and can be minimized by elimination of CpG motifs in the vector genome. Further, a CpG-depleted vector expressing human coagulation factor IX showed markedly reduced (albeit not entirely eliminated) CD8+ T cell infiltration upon intramuscular gene transfer in hemophilia B mice when compared to conventional CpG+ vector (comprised of native sequences). Therefore, this deimmunization strategy is helpful in reducing the potential for CD8+ T cell responses to capsid or transgene product. However, CpG depletion had minimal effects on antibody responses against capsid or transgene product, which appear to be largely independent of CpG motifs.